Protein arginine deiminase 4 inhibition is sufficient for the amelioration of collagen-induced arthritis. (9th March 2017) - Willis, V C; Banda, N K; Cordova, K N; Chandra, P E; Robinson, W H; Cooper, D C; Lugo, D; Mehta, G; Taylor, S; Tak, P P; Prinjha, R K; Lewis, H D; et al.
Summary: Citrullination of joint proteins by the protein arginine deiminase (PAD) family of enzymes is recognized increasingly as a key process in the pathogenesis of rheumatoid arthritis. This present study was undertaken to explore the efficacy of a novel PAD4-selective inhibitor, GSK199, in the murine collagen-induced arthritis model of rheumatoid arthritis. Mice were dosed daily from the time of collagen immunization with GSK199. Efficacy was assessed against a wide range of end-points, including clinical disease scores, joint histology and immunohistochemistry, serum and joint citrulline levels and quantification of synovial autoantibodies using a proteomic array containing joint peptides. Administration of GSK199 at 30 mg/kg led to significant effects on arthritis, assessed both by global clinical disease activity and by histological analyses of synovial inflammation, pannus formation and damage to cartilage and bone. In addition, significant decreases in complement C3 deposition in both synovium and cartilage were observed robustly with GSK199 at 10 mg/kg. Neither the total levels of citrulline measurable in joint and serum, nor levels of circulating collagen antibodies, were affected significantly by treatment with GSK199 at any dose level. In contrast, a subset of serum antibodies reactive against citrullinated and non-citrullinated joint peptides were reduced with GSK199 treatment. These data extend our previous demonstration of efficacy with the pan-PAD inhibitor Cl-amidine and demonstrate robustly that PAD4 inhibition alone is sufficient to block murine arthritis clinical and histopathological end-points. Graphical Abstract: